305 Surgical complexity and intra-operative fluid management influence duration of ICU care following cytoreductive surgery. (13th November 2020) - Collins, A; Spooner, S; Horne, J; Chainrai, M; Moss, E; Davies, Q; Chattopadhyay, S; Bharathan, R
Abstract : Introduction: Increased routine radical cytoreductive surgery for advanced ovarian cancer has resulted in higher utilisation of intensive care settings for post-operative recovery. We aimed to identify peri-operative variables associated with extended ICU admission. Methods: A retrospective review of all patients admitted to the ICU following cytoreductive surgery for ovarian cancer in a tertiary referral centre from 2015–2019. Patients were categorised according to length of stay, <48 hours and ≥48 hours. Peri-operative variables were compared using student's t-test or Fischer's exact test. Results: 56 patients were admitted to the ICU immediately post-operatively, 37 for <48h and 19 for ≥48h (range 3–11 days). There were no differences between cohorts in terms of median age, BMI, Charleston co-morbidity index or whether the patient had received NACT. Intra-operative predictors of prolonged ITU stay included extended duration of surgery (313 v 242 mins, p=0.020), higher surgical complexity score (5.6 v 4.1, p=0.016), bowel resection (63.2% v 32.4%, p=0.045), extensive intra-operative fluid use (6071 v 3789 ml, p=0.0002), intra-operative blood transfusion (63.2 v 32.4%, p=0.045) and higher estimated blood loss (1594 v 835 ml, p=0.013). Post-operative variables associated with prolonged ITU admission included higher immediate post-operative lactate (2.31 v 1.56, p=0.031), lower post-operative albumin (23.5 v 28.5, p=0.018) or eGFR (74 v 83, p=0.028) and need for post-operative blood transfusion (89.5 v 40.54%, p=0.005). Conclusions: Utilising identified intra-operative risk factors to perform individualised risk assessments for prolonged ICU admission could be used to assist communication between surgeons and intensivists to improve planning of ICU resources.